Motivation From The Perspective Of Eastern Islamic Philosophy: A Synthesis Of Mulla Sadra And Al-Ghazali's Thought In The Context Of Contemporary Work Ethos - Rachman, Faizal; Suraji, Robertus (OGZ Research & Publishing, 2025)
This study explores the contribution of Eastern Islamic philosophy to the modern concept of work motivation. Employing a qualitative approach grounded in philosophical literature analysis, it synthesizes Mulla Sadra’s notions of substantial motion (al-harakah al-jawhariyyah) and existential perfection, alongside Al-Ghazali’s teachings on intention (niyyah), sincerity (ikhlas), and spiritual stations (maqamat) in labor. The findings indicate that motivation should not be viewed merely as a psychological or material drive, but rather as an existential journey toward spiritual perfection. Work is thus positioned as a form of worship with transcendent value, particularly when rooted in pure intention, awareness of divine responsibility, and the pursuit of inner meaning. This synthesis offers a new paradigm of work motivation that balances worldly objectives with spiritual aspirations, making it relevant for the ethical framework of both public and private sector organizations.